Organic carbon stocks of Great British saltmarshes - Smeaton, Craig; Ladd, Cai J. T.; Miller, Lucy C.; McMahon, Lucy; Garrett, Ed; Barlow, Natasha L. M.; Gehrels, W. Roland; Skov, Martin W.; Austin, William E. N. (Frontiers in Marine Science, 2023)
Coastal wetlands, such as saltmarshes, are globally widespread and highly effective at capturing and storing ‘blue carbon’ and have the potential to regulate climate over varying timescales. Yet only Australia and the United States of America have national inventories of organic carbon held within saltmarsh habitats, hindering the development of policies and management strategies to protect and preserve these organic carbon stores. Here we couple a new observational dataset with 4,797 samples from 26 saltmarshes across Great Britain to spatially model organic carbon stored in the soil and the above and belowground biomass of Great British saltmarshes. Using average values derived from the 26 marshes, we deliver first-order estimates of organic carbon stocks across Great Britain’s 448 saltmarshes (451.66 km2). The saltmarshes of Great Britain contain 5.20 ± 0.65 Mt of organic carbon, 93% of which is in the soil. On average, the saltmarshes store 11.55 ± 1.56 kg C m-2 with values ranging between 2.24 kg C m-2 and 40.51 kg C m-2 depending on interlinked factors such as geomorphology, organic carbon source, sediment type (mud vs sand), sediment supply, and relative sea level history. These findings affirm that saltmarshes represent the largest intertidal blue carbon store in Great Britain, yet remain an unaccounted for component of the United Kingdom’s natural carbon stores.